Common Sense, Reasoning, and Rationality 2002
DOI: 10.1093/0195147669.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Ending the Rationality Wars How to Make Disputes about Human Rationality Disappear

Abstract: This chapter focuses on the two opposing sides of the current rationality wars with the “heuristics and biases” researchers on the one hand, and the evolutionary psychologists on the other. The former group cites decades of evidence that people have systematic deviations from rationality, as evidenced by their performance on certain types of formal reasoning tasks. The latter group asserts the implausibility of the human architecture evolving with an inaccurate sense of probability and offers evidence that a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(72 citation statements)
references
References 24 publications
2
63
0
7
Order By: Relevance
“…4 Nous parlons ici de la psychologie évolutionniste en général, et non de la seule « école » autour de Cosmides et de Tooby (voir Marcus, 2008 : 6-9;Stanovich, 2004 : chapitre 5). 5 Ceci suggère, comme le défendent Samuels, Stich et Bishop (2002), que la différence entre une position comme celle de Stanovich et une position comme celle de Gigerenzer n'est pas si importante : c'est principalement une différence d'emphase. 6 Les illusions d'optique permettent d'illustrer cette idée : bien que nous sachions qu'une image est une illusion, nous continuons tout de même de percevoir cette illusion.…”
Section: E S a T E L I E R S D E L ' é T H I Q U E / T H E E T H I unclassified
“…4 Nous parlons ici de la psychologie évolutionniste en général, et non de la seule « école » autour de Cosmides et de Tooby (voir Marcus, 2008 : 6-9;Stanovich, 2004 : chapitre 5). 5 Ceci suggère, comme le défendent Samuels, Stich et Bishop (2002), que la différence entre une position comme celle de Stanovich et une position comme celle de Gigerenzer n'est pas si importante : c'est principalement une différence d'emphase. 6 Les illusions d'optique permettent d'illustrer cette idée : bien que nous sachions qu'une image est une illusion, nous continuons tout de même de percevoir cette illusion.…”
Section: E S a T E L I E R S D E L ' é T H I Q U E / T H E E T H I unclassified
“…The phenomenon prompted an enormous amount of research work in psychology and beyond, like many others achievements from Tversky and Kahneman's research programme, which readily and steadily attracted interest from philosophers (Levi 1985;Stich 1990;Samuels, Stich and Bishop 2002) and also established the new interdisciplinary field of behavioural economics (Camerer, Loewenstein and Rabin 2003).…”
Section: Case-study Ii: the Conjunction Fallacymentioning
confidence: 99%
“…Evaluating this response requires assessing whether the rationality of a decision is determined by the process of decision-making or the outcome [10,24]. In short, the defense of (P) considered here depends on seeing rationality as based on an evaluation of the process, where a fully rational decision is one where the individual understands the relevant outcomes, probabilities, and utilities, and then uses them to calculate and maximize expected utility.…”
Section: Accounts Of Rationalitymentioning
confidence: 99%
“…Research has shown that humans perceive risk and choose actions in ways that rarely conform to the strict standards assumed by the Standard Picture [10,24]. As mentioned in the discussion of the dual representation model above, individuals appear to make decisions partly based on their general sense of the significance of the risk, separate from any quantitative representation of its magnitude [3,5,7].…”
Section: Accounts Of Rationalitymentioning
confidence: 99%
See 1 more Smart Citation